The Paradox Of Distance Education - Forte, Glenn J.; Schwandt, David R.; Swayze, Susan; Butler, Joan; Ashcraft, Merrill (European Scientific Journal, ESJ, 2016)
Over the last several years distance education (DE) class offerings at U.S. universities and colleges have been increasing at a rate of approximately 10% or more per year (Allen & Seaman, 2014). While the effectiveness of DE courses vis-à-vis face-to-face (F2F) courses has been sufficiently documented, there are few studies that compare student evaluations of the two class delivery systems. Therefore, we sought to answer the question, is there a significant difference between student evaluations of the teaching methods and styles (TM&S) of DE and F2F classes as measured on a student completed class and instructor survey, examined through the lens of Moore’s Transactional Distance Theory’s (TDT) constructs of student autonomy, dialogue and structure (1997, 2010, 2012)? Moore maintains that DE is not only a geographical separation of student and teacher; it is also a psychological and pedagogical separation. The twenty TM&S questions included in the survey data for 765 classes offered from September 6, 2011 to December 19, 2013 were collected and analyzed for classes identified as SOC 101 Introduction to Sociology through SOC 340 Applied Research in the Behavioral Sciences that are offered by the College of Social and Behavioral Sciences at a Mid-Atlantic Open University. A t-test analysis of variance was conducted and analyzed. The results of the study indicate that 16 of the 20 TM&S questions returned statistically significant results, 3 of 4 for student autonomy, 8 of 10 for dialogue and 5 of 6 for structure. Three of the TDT construct dialogue/interaction questions and 2 of the TDT construct structure questions returned medium effect size magnitudes. Three of the TM&S questions associated with the TDT construct autonomy returned statistically significant results with low effect size magnitudes. Based on the results of the study, we have concluded that psychological and pedagogical separation, or TD between student and teacher is reduced when the DE course structure encourages and requires increased dialogue and interaction. Moreover, we found that student autonomy does not play a significant role in reducing TD in computer mediated DE courses.